NGOs, political protest, and civil society - Boulding, Carew (New York : Cambridge University Press, 2014)
This book argues that non-governmental organizations (NGOs) have an important effect on political participation in the developing world. Contrary to popular belief, they promote moderate political participation through formal mechanisms such as voting only in democracies where institutions are working well. This is a radical departure from the bulk of the literature on civil society that sees NGOs and other associations as playing a role in strengthening democracy wherever they operate. Instead, Carew Boulding shows that where democratic institutions are weak, NGOs encourage much more contentious political participation, including demonstrations, riots, and protests. Except in extreme cases of poorly functioning democratic institutions, however, the political protest that results from NGO activity is not generally anti-system or incompatible with democracy - again, as long as democracy is functioning above a minimal level.
Machine generated contents note: 1. Introduction; 2. NGOs, mobilization, participation, and democracy; 3. Local NGO activity and its consequences in Bolivian municipalities; 4. NGOs, associations, protest, and voting in Latin America; 5. Associational activity and participation in developing democracies; 6. Civil society, protest, and attitudes toward democracy; 7. Conclusions: articulating democratic discontent.
Title from publisher's bibliographic system (viewed on 14 Jan 2016).
Keywords: Non-governmental organizations -- Political activity -- Developing countries; Political participation -- Developing countries; Civil society -- Developing countries; Protest movements -- Developing countries; Democracy -- Developing countries